Treasures 5: The West (1898-1938), Program 3 - VanDyke, Woodbridge Strong; Tilghman, William; Kent, James Bennie; Cronjager, Edward; Welty, Chuck; Mix, Tom; Dix, Richard; Ralston, Esther (National Film Preservation Foundation, 2011)
The West has long held pride of place in motion pictures, both as a production center and as the inspiration for that most American of film genres. For audiences today, it is easy to assume that early movies set in the region were just like the sound Westerns that followed. But the films saved by archives tell a far different story. In the years before the "classic" Western, films about the West were as wide open as the region itself. "Treasures 5" brings together 40 early movies showing the West as it's never been seen on DVD. [www.filmpreservation.org]
Keywords: DVD-Video